Developing a Causally Valid Picture-Story Measure of Sexual Motivation: I. Effects of Priming - Hinzmann, Jessica; Khalaidovski, Ksenia; Kullmann, Jennifer S.; Brummer, Julian; Braun, Sinja; Kurz, Petra; Wagner, Katharina M.; Schultheiss, Oliver (Motivation Science, 2023)
Sexual motivation plays a crucial role in both normal sexual functioning as well as sexual dysfunctions. Although many self-report questionnaires exist to assess sexual motivation, their validity is restricted in that their sensitivity to experimental manipulation has not been tested and that they are subject to self-report limitations (e.g., self-representational issues). The aim of the current research is to develop and validate through experimental means a measure of sexual motivation based on the content analysis of imaginative stories that participants write about socially ambiguous pictures. In two studies (Study 1: N = 86; Study 2: N = 113), participants were randomly allocated to an erotic prime or control prime condition and took a picture-story test before and after the presentation of the primes. Subjective affect was assessed in both studies; physiological measures of affect (pupillometry and facial electromyography) and a criterion measure of sexual motivation (key-pressing for longer exposure to sexual vs. control pictures) only in Study 2. In both studies, erotically primed participants showed an increase of sexual imagery in picture stories, whereas participants presented with control primes did not. In Study 2, this effect was mediated by subjective and physiological arousal. Sexual imagery changes also mediated the effect on the behavioral criterion (viewing time for sexual pictures). We additionally report evidence for the discriminant validity of the sexual motive arousal procedure.
CRIS-Team Scopus Importer:2024-12-16
Keywords: causal validation; picture-story exercise; priming; sexual motivation

Development of a Causally Valid Measure to Assess Sexual Motivation - Hinzmann, Jessica; Schultheiss, Oliver (INTERNATIONAL JOURNAL OF SEXUAL HEALTH, 2019)
CRIS-Team WoS Importer:2019-10-29

Implicit Measures in Clinical Sex Research: A Critical Evaluation - Hinzmann, Jessica; Borg, Charmaine; de Jong, Peter J. (Sexual Medicine Reviews, 2020)
Introduction: Current information-processing models of sexual arousal imply that both controlled and automatic affective-motivational processes are critically involved in sexual responding and suggest that dysfunctional automatic processes may be involved in the development and persistence of sexual dysfunctions. Because (dysfunctional) automatic processes and responses cannot be adequately captured by common self-report measures, implicit performance-based measures have been developed to index these processes. Objectives: This review provides an overview of studies that used implicit tasks in clinical sexual research, and critically evaluates the contribution and promise of these measures to improve our understanding of the mechanisms involved in sexual dysfunctions. Methods: 6 electronic main databases (AMED, MEDLINE, PsycArticles, Psychology & Behavioral Sciences Collection, PsycINFO, and SocINDEX) were searched for studies involving implicit measurement techniques to measure automatic processes in clinical sex research. Results: A series of studies examined if lowered (or heightened) attention for sex stimuli may be involved in low sexual arousal, low desire, and genital pain. Preliminary evidence showed that lowered attention is involved in low sexual arousal. The pattern with regard to desire and genital pain was mixed which may be due to heterogeneity in assessment instruments. A limited number of studies examined automatic memory associations with sexual cues. Preliminary evidence showed negative (sex-threat/sex-disgust) associations in women with genito-pelvic pain or penetration disorder, less positive associations in women with hypoactive sexual desire disorder, and sex-positive and sex-failure associations in men with sexual distress. Thus far, no studies have examined lowered (or heightened) automatic sexual approach tendencies related to sexual dysfunctions. Conclusion: Implicit measures showed some promise as tools to index automatic sex-relevant cognitive mechanisms in sexual dysfunctions. Yet, more systematic research and the development of psychometrically sound measures are critical for a more comprehensive evaluation of the relevance of implicit measures in clinical sex research and their usefulness as indices of individual differences in clinical practice. Hinzmann J, Borg C, de Jong PJ. Implicit Measures in Clinical Sex Research: A Critical Evaluation. Sex Med Rev 2020;XX:XXX–XXX.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Automatic Processes; Clinical Sex Research; Implicit Tasks; Sexual Dysfunctions

RESEARCH METHODS IN MOTIVATION SCIENCE; Developing a Causally Valid Picture-Story Measure of Sexual Motivation: II. Effects of Film Clips - Schultheiss, Oliver; Hinzmann, Jessica; Bergmann, Sara; Matthes, Manuel; Beyer, Bastian; Janson, Kevin (Motivation Science, 2023)
Replicating and extending previous work by Hinzmann et al. (in press), the present research aimed at validating a picture-story measure of sexual motivation, termed need for sex (n Sex). In two experimental studies (Ns = 154 and 171) with repeated-measures design, we showed that (a) n Sex is sensitive to experimental manipulation of sexual motivation via film clips, (b) that this effect is mediated by increased subjective arousal as an indicator of a motivational process, and (c) that the part of n Sex variance that is sensitive for experimental manipulation is also the one accounting for variations in a behavioral criterion (key pressing and viewing time measures of relative preference for erotic over nonerotic pictures). These effects emerged specifically when film clips portrayed sex positively, but not when they showed sex with embarrassing or threatening consequences. As a dispositional measure, n Sex correlated positively with self-report measures of sexual desire and behavior. But it did not feature the sex difference associated with these measures and retained incremental validity above and beyond them for behavioral criterion measures.
CRIS-Team Scopus Importer:2023-09-08
Keywords: content coding; picture-story measure; sexual motivation; thematic apperception; validation

The Reciprocal Relationship Between Sexual Arousal and Disgust as Evidenced in Automatic Approach-Avoidance Behavior - Hinzmann, Jessica; Borg, Charmaine; Verwoerd, Johan R. L.; De Jong, Peter J. (Journal of Sex Research, 2019)
Sexual encounters imply exposure to stimuli that in other contexts typically elicit disgust-induced avoidance. To explain why people nevertheless tend to show sexual approach, it has been proposed that heightened sexual arousal may temporarily inhibit disgust. In line with this, studies have found that sexually aroused individuals showed heightened willingness to approach disgusting stimuli. Because automatic processes are critically involved in sexual behaviors, we examined whether the impact of sexual arousal extends to automatic responses to disgust-elicitors. To test the proposed reciprocal relationship between sex and disgust, we also investigated whether disgust reduces automatic sexual approach. In Study 1, 116 female participants (M = age 19.53) were assigned to a sexual arousal or control condition and performed a speeded approach-avoidance task to assess automatic responses to disgusting stimuli. In Study 2, 174 female participants (M = age 22.14) were assigned to a disgust, sexual arousal, or control condition and performed an approach-avoidance task involving both sex and disgust-relevant stimuli. Sexual arousal did not affect automatic responses to disgusting stimuli, and disgust did not influence automatic responses towards sexual stimuli. The reciprocal relationship between sexual arousal and disgust that was previously found for controllable responses did not extend to automatic responses.
CRIS-Team WoS Importer:2019-09-24